Impact Analysis of Trim Tab Inclination Angles Variation to Propulsion Power Requirement of 6 Meterâ€™s Speed Boat - Amiadji, Amiadji; Baidowi, Achmad; Nanda Oktova, Aufal (Institut Teknologi Sepuluh Nopember, 2021)
Determining the ship's propulsion power requirements is one of the most crucial things in ship design which is related to the ship's resistance. One of the causes of the high value of a ship's resistance is excessive trim of the ship. Therefore it needs a mechanism to overcome this, it can be by applying trim tabs. The trim tab is a small surface mounted on the ship's transom that can be adjusted according to the conditions of the ship. By adjusting the angle of the trim tab to be larger, it can increase the lift force and torque moment at the stern of the ship which can reduce the trim of the ship. Based on the boatâ€™s characteristics, referring to the guide from Bennet Marine, the appropriate trim tabâ€™s geometry for this boat is a trim tab with a span width of 18â€ (46 cm) and a chord length of 9â€ (23 cm). After selecting the trim tab geometry, then analyzing the resistance and trim of the ship using the CFD method. Through CFD simulation, trim tab with an angle of 15â° can reduce the value of the ship's resistance to 17.25% and for the trim can be reduced to 46.72%. Then after the ship's propulsion power requirements calculation, it is shown that the trim tab with an angle of 15â°, a reduction of 11.56% is obtained from 78.854 kW to 69.741 kW.